EVALUASI SISTEM PENDUKUNG KEPUTUSAN TUBERKULOSIS DI PUSKESMAS BERBASIS KEWILAYAHAN: STUDI CROS-SECTIONAL DI SUKOHARJO, JAWA TENGAH, INDONESIA - Setiyadi, Noor Alis; Febriyanto, Dwi Ferry; Wulandari, Respati; Hudayani, Rina; Setyowati, Maryani (Dian Nuswantoro Semarang, 2025)
The lack of a decision support system for the Tuberculosis or TB Program implemented in the Sukoharjo Regency Office has resulted in a gap or mismatch between the estimated number of TBC cases and the discovery of TBC cases in the field so that the decisions taken so far are only based on the discovery of existing TBC cases. The purpose of this study was to evaluate the use of SPK-TB in supporting the village-based Tuberculosis Suspect Screening Program. The research method used the Mix-method method which combines qualitative and quantitative research types. The research subjects consisted of 12 TBC information system users at the public health center and the Health Office. The results showed that the system that had been developed and tested at each user level, especially the head of the health centre, was well accepted and used as intended. This shows that system acceptance before and after testing with the TAM method has increased the average value. It is recommended that this SPK-TB be implemented immediately so that the effectiveness and efficiency of the performance of TBC officers and the Health Office can be known.